2010
DOI: 10.1080/01446191003674519
|View full text |Cite
|
Sign up to set email alerts
|

Cost and time control of construction projects: inhibiting factors and mitigating measures in practice

Abstract: Despite the availability of various control techniques and project control software many construction projects still do not achieve their cost and time objectives. Research in this area so far has mainly been devoted to identifying causes of cost and time overruns. There is limited research geared towards studying factors inhibiting the ability of practitioners to effectively control their projects. To fill this gap, a survey was conducted on 250 construction project organizations in the UK, which was followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
226
2
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(280 citation statements)
references
References 31 publications
12
226
2
15
Order By: Relevance
“…In the works of Olawale & Sun [3], the recurring helplessness of research efforts towards decimating cost and time of construction project delivery failure was resonated in their presentation, that despite the availability of various control techniques and project control software, many construction projects still do not achieve their cost and time objectives. They posited that research effort has only been central to the investigation of causes rather than factors inhibiting effective control of project.…”
Section: Research Responses To Poor Project Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In the works of Olawale & Sun [3], the recurring helplessness of research efforts towards decimating cost and time of construction project delivery failure was resonated in their presentation, that despite the availability of various control techniques and project control software, many construction projects still do not achieve their cost and time objectives. They posited that research effort has only been central to the investigation of causes rather than factors inhibiting effective control of project.…”
Section: Research Responses To Poor Project Performancementioning
confidence: 99%
“…The Olawale & Sun [3] study precipitated 90 Mitigating measures against top five leading factors of design changes, risk/uncertainties, in accurate evaluation of project time/ duration complexities and non-performance of sub contractors. Against this backdrop, a confine point of what causes over runs in construction projects was them identified by the vacuum between inexperience project management factor and low skilled manpower factor used in construction projects.…”
Section: Research Responses To Poor Project Performancementioning
confidence: 99%
See 1 more Smart Citation
“…These changes over and over again lead to rework [2] which can degrade the project performance [3]. Without proper change management strategy [4], undesired design changes will result in unexpected rework which lead to delays and disruptions [5]. Delays and disruptions have negative effects on construction project performance [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Olawale and Sun [4] revealed that construction projects globally share some key characteristics. This is further supported by Abdul-Rahman et al [11] in the synthesis of preceeding studies where design changes have been named as the critical factor for project delays and cost overuns in construction project at different parts of the world.…”
Section: Introductionmentioning
confidence: 99%